2015
DOI: 10.4103/1305-7456.156846
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the Greulich and Pyle atlas when applied to a Southern Turkish population

Abstract: Objective:The aim of this study was to evaluate the applicability of Greulich and Pyle (GP) method for Southern Turkish population.Materials and Methods:Hand and wrist radiographs of 535 patients (276 females, 259 males aged from 10 to 18 years) selected retrospectively from the archive. Skeletal age (SA) estimation was performed according to GP atlas. The chronological age (CA) and SA were compared using the Paired t-test.Results:The mean difference between the CA and SA ranged from 0.07 to 1.11 years. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The subjects were classified into 3 growth periods: the pre-peak, peak, and post-peak growth periods, using handwrist maturation stages as determined by the Greulich-Pyle method 19. The pre-peak growth period was defined as the period when the epiphysis of the proximal phalanx of the index finger was of the same width as the diaphysis (PP2), when the epiphysis of the middle phalanx of the middle finger was of the same width as the diaphysis (Mp3), and by the first mineralization of the ulnar sesamoid bone (S).…”
Section: Methodsmentioning
confidence: 99%
“…The subjects were classified into 3 growth periods: the pre-peak, peak, and post-peak growth periods, using handwrist maturation stages as determined by the Greulich-Pyle method 19. The pre-peak growth period was defined as the period when the epiphysis of the proximal phalanx of the index finger was of the same width as the diaphysis (PP2), when the epiphysis of the middle phalanx of the middle finger was of the same width as the diaphysis (Mp3), and by the first mineralization of the ulnar sesamoid bone (S).…”
Section: Methodsmentioning
confidence: 99%
“…A further limitation of the study is the failure to calculate the mean absolute and root mean square errors, which might have further confirmed the accuracy of the G&P atlas in relation to each population. However, the mean of each variable (BA and CA) was only available for 13 studies [18, 19, 24, 26–28, 35, 38, 49–53], and for these 13 studies, individual observations were not provided; therefore, the mean error could not be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…However, other authors recommend that the G&P atlas be used with reservation due to mean BA being retarded in some age groups compared to the reference population [2932]. Common findings among these studies of the G&P atlas include underestimation of males aged below 13 years and overestimation during adolescence [3036]. G&P was applicable to females during adolescence while overestimation was reported before the age of 12 years [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…G&P was applicable to females during adolescence while overestimation was reported before the age of 12 years [31, 32]. Others have recommended that a new standard altogether is required for precise bone age assessment, given the significant advancement of BA due to secular changes in skeletal maturation, which is thought to be due to improved standard of living [28, 30, 35, 36]. For example, Calfee et al reported that G&P overestimated males and females between 12 and 15 years old, for whom BA exceeded CA by at least 2 years [35].…”
Section: Discussionmentioning
confidence: 99%